2023
DOI: 10.1158/1538-7445.sabcs22-pd11-10
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD11-10: PD11-10 Efficacy, Safety, and Tolerability of KN046 (an anti-PD-L1/CTLA-4 Bispecific Antibody) in combination with Nab-paclitaxel in Metastatic Triple-negative Breast Cancer (mTNBC):Final results of the Phase II trial

Abstract: Background: Despite recent FDA approval of immune checkpoint inhibitor pembrolizumab and drug-antibody conjugate in the treatment of mTNBC, the overall survival benefit of these patients remains modest. We conducted a phase 2 study to assess the efficacy and safety of anti-PD-L1/CTLA-4 bispecific antibody KN046 in combination with nab-paclitaxel in mTNBC patients (pts) regardless of PD-L1 status. Preliminary results have been delivered in 2021 AACR[1], here we reported the final results of the progression-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the present multicenter, open-label, phase II study, we evaluated the efficacy and safety of KN046 plus nab-paclitaxel in the first-line treatment of locally advanced inoperable or metastatic TNBC patients. To our knowledge, this study represents the initial investigation assessing the use of bispecific antibodies as a first-line treatment for advanced TNBC, and the preliminary and final results of the present study have been reported in the American Association for Cancer Research (AACR) 2021 and the San Antonio Breast Cancer Symposium (SABCS) 2022 previously 18 , 19 . Consistent with the preliminary analysis 18 , the final analysis showed favorable clinical efficacy and survival benefits with the treatment of KN046 plus nab-paclitaxel.…”
Section: Discussionmentioning
confidence: 96%
“…In the present multicenter, open-label, phase II study, we evaluated the efficacy and safety of KN046 plus nab-paclitaxel in the first-line treatment of locally advanced inoperable or metastatic TNBC patients. To our knowledge, this study represents the initial investigation assessing the use of bispecific antibodies as a first-line treatment for advanced TNBC, and the preliminary and final results of the present study have been reported in the American Association for Cancer Research (AACR) 2021 and the San Antonio Breast Cancer Symposium (SABCS) 2022 previously 18 , 19 . Consistent with the preliminary analysis 18 , the final analysis showed favorable clinical efficacy and survival benefits with the treatment of KN046 plus nab-paclitaxel.…”
Section: Discussionmentioning
confidence: 96%